Jejak Kiprah MONUSCO dalam Merajut Perdamaian di Republik Demokratik Kongo (2020-2021) - Bundu, Priskila Arta; Renitha Dwi Hapsari (Department of International Relations, Brawijaya University, 2023)
Abstract Civil war that occurred in RD Congo causes the dynamics of conflict in various sectors. This causes human rights violations, the death of civil society, infrastructure damage and government failure in running its function. Responding this situation, UN as an international organization has responsibility to protect conflicting countries. The UN Security Council took step to send Monusco security forces to RD Congo with the aim of running security and peace mission. Monusco did his mission with the peacekeeping and peacebuilding concept approach that introduced by Johan Galtung is supposed to protect civil society. This paper uses a qualitative type with descriptive method to explain Monusco's performance during RD Congo by 2020 to 2021. The Monusco's attempt is assisted with collaboration with organizations and other security communities. The military forces efforts in handling rebel groups strongly support the process of protection and evacuation of civil society. Although it suffered enough failures due to unpredictable but the Monusco security forces were able to run many security missions for civil society. Keywords: MONUSCO, Peacekeeping, Peacebuilding Abstrak Perang sipil yang terjadi di RD Kongo menyebabkan dinamika konflik di berbagai sektor. Hal ini menyebabkan pelanggaran HAM, kematian masyarakat sipil, kerusakan infrastuktur dan kegagalan pemerintah dalam menjalankan fungsinya. Merespon hal ini PBB sebagai organisasi internasional memiliki tanggung jawab untuk melindungi negara yang berkonflik. Dewan Keamanan PBB mengambil langkah tegas mengirimkan pasukan keamanan MONUSCO ke RD Kongo dengan tujuan menjalankan misi keamanan dan perdamaian. MONUSCO melakukan misinya dengan pendekatan konsep peacekeeping dan peacebuilding yang dipopulerkan oleh Johan Galtung berfokus untuk melindungi masyarakat sipil. Tulisan ini menggunakan tipe kualitatif dengan metode deskriptif untuk menjelaskan kinerja MONUSCO selama di RD Kongo pada tahun 2020 hingga 2021. Upaya MONUSCO dibantu dengan kolaborasi bersama organisasi dan komunitas keamanan lainnya. Upaya pasukan militer dalam menangani kelompok pemberontak sangat mendukung proses perlindungan dan evakuasi masyarakat sipil. Meskipun cukup mengalami beberapa kegagalan akibat hal yang tidak terprediksi tetapi pasukan keamanan MONUSCO mampu menjalankan banyak misi keamanan bagi masyarakat sipil. Kata Kunci: MONUSCO, Peacekeeping, Peacebuilding